Readership of Free Community Papers as a Source of Advertising Information: A Uses and Gratifications Perspective - Tsao, James C. and Sibley, Stanley D. (Journalism & Mass Communication Quarterly, 2004)
The free paper is a convenient and relevant advertising information source, performing the functions of providing surveillance information and product values to consumers. Several market segments with varying market attributes are identified as heavy readers of the free paper. Based on the theoretical framework of uses and gratifications, a multivariate model helps to explain readership. Readership of the free paper increases as age increases, as involvement in some leisure lifestyles increases, as more favorable attitude toward the free paper increases, and as the value of information on homes and equipment and on food and supplies increases.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDc3Njk5MDA0MDgxMDA0MDQ